Kinetic Study of Sulforaphane Stability in Blanched and Un-Blanched Broccoli (Brassica Oleracea Var. Italica) Florets During Storage at Low Temperatures - Saavedra-Fenoglio, A; Mahn-Osses, A (Springer, 2018)
Sulforaphane is a health-promoting compound found in broccoli. Given its high thermo-lability, its preservation through high-temperature processes seems inconvenient. Accordingly, storage at low temperature is an alternative. There are no studies about the evolution of sulforaphane content during storage at low temperatures. The change of sulforaphane content in blanched and un-blanched broccoli florets during storage at 10, − 1, − 21 and − 45 °C for 83 days was studied. In blanched broccoli, sulforaphane content followed a first-order degradation kinetics (R2 ≥ 0.95). A two-consecutive irreversible reactions model described adequately the evolution of sulforaphane content in un-blanched broccoli (R2 ≥ 0.94). Activation energies from Arrhenius equation resulted in 19.4 kJ/mol for blanched and 30 kJ/mol (formation) and 58 kJ/mol (degradation) for un-blanched broccoli. Storage of un-blanched broccoli at − 45 °C for 40 days maximized sulforaphane content. These results could be useful to propose broccoli storage conditions that preserve or maximize sulforaphane content. © 2018, Association of Food Scientists & Technologists (India).